PENGARUH HARGA, KUALITAS PRODUK, LOKASI DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN SERABI BANDUNG “PELANGI” DI MOJOKERTO - Ichwan Bagus Airlangga; Jamianto Jamianto; Ali Mahsun (Fakultas Ekonomi Universitas Yos Soedarso, 2020)
This study aims to analyze the effect of price, product quality, location and promotion on purchasing decisions. The research method used is a quantitative method. This study uses purposive sampling. The sample in this study amounted to 50 respondents. Data collection instrument using a questionnaire. The dependent variable is the purchase decision variable and the independent variable is price, product quality, location and promotion, namely price, product quality, location and promotion on the purchasing decision of Serabi Bandung